CODE-SWITCHING AND CODE-MIXING PHENOMENA IN ENGLISH LEARNING PROCESS AT THE DEPARTMENT OF ENGLISH EDUCATION - Rahmanika, Febria; Anastasia, Faurina (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
Based on the preliminary research, the researcher found that English students commonly used codeswitching and code-mixing during the English learning process at the Department of EnglishEducation UIN Suska Riau. The researcher aimed: 1) to investigate the types of code-switching andcode-mixing, and 2) to find out why the students used those codes in the English learning process.This research used a qualitative descriptive method. The data was collected from the fifth semesterof English Education students selected based on purposive sampling technique. The finding of thisstudy showed that the students uttered three types of code-switching, such as inter-sentential, intrasentential, and tag switching. Then, there are two types of code-mixing uttered by the sample, suchas intra-sentential mixing and intra-lexical mixing. Furthermore, the reasons for uttering those codesare; 1) talking about a particular topic, 2) repetition for clarification, 3) the intention of clarifyingthe speech content for the interlocutor, 4) English as a foreign language, and 5) the student lessconfidence when speaking.